1992
DOI: 10.1109/42.126905
|View full text |Cite
|
Sign up to set email alerts
|

Vector-extrapolated fast maximum likelihood estimation algorithms for emission tomography

Abstract: A new class of fast maximum-likelihood estimation (MLE) algorithms for emission computed tomography (ECT) is developed. In these cyclic iterative algorithms, vector extrapolation techniques are integrated with the iterations in gradient-based MLE algorithms, with the objective of accelerating the convergence of the base iterations. This results in a substantial reduction in the effective number of base iterations required for obtaining an emission density estimate of specified quality. The mathematical theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 31 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…One of the main reasons for this is that EM algorithms have very slow convergence speed and thus a large number of iterations may be required to obtain an acceptable reconstructed Manuscript image. Several modifications have been suggested to accelerate the convergence of these algorithms using line search [11] and vector extrapolation [14] techniques. Other fast alternatives have also been proposed to speed up the convergence.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons for this is that EM algorithms have very slow convergence speed and thus a large number of iterations may be required to obtain an acceptable reconstructed Manuscript image. Several modifications have been suggested to accelerate the convergence of these algorithms using line search [11] and vector extrapolation [14] techniques. Other fast alternatives have also been proposed to speed up the convergence.…”
Section: Introductionmentioning
confidence: 99%
“…The object space is a square region inscribed within the circle of detectors. To exploit the eight-fold symmetry we have assumed the object to be bounded by a circle inscribed in this square object space [10] [11]. An electron-positron annihilation event occurring inside a pixel is governed by a number of physical phenomena such as attenuation, scattering, absorption and detector characteristics.…”
Section: Simulated Experimental Results On Pet Systemmentioning
confidence: 99%
“…It is found that using symmetry available in the system the data size of P matrix can be reduced considerably [10]. For simulating measurement data, a Monte Carlo procedure is used [1] [11]. Shepp and Logan mathematical phantom with 100,000 emissions has been used for simulation studies.…”
Section: Simulated Experimental Results On Pet Systemmentioning
confidence: 99%
“…Each element of probability matrix pi, is the probability of an annihilation event in pixel i, getting detected in the j t h detector and is taken as the angle seen by the center of pixel i into the detector tube j . For simulating measurement data, a Monte Carlo procedure is used [1] [9]. Shepp-Logan mathematical phantom with 100,000 emissions has been used for the present simulation studies.…”
Section: Simulated Experimental Resultsmentioning
confidence: 99%